The Value Logic of Modernization of Chinese Folk Sports -Taking the custom of Dinghuo dragon dance as Case Study - Chen, Cheng; Zheng, GuoHua (Journal of Roi Kaensarn Academi, 2023)
The modernization of folk sports is a multi-dimensional process of change, and its core is to realize the modernization of people. In practice, the modernization of folk sports is easy to fall into the value crisis of the imbalance between tool and purpose. Ding gang dragon dance custom is an excellent and representative folk sports project and intangible cultural heritage project in China, with a history of 2000 years and strong local cultural characteristics. Based on the value theory, this study adopts the field investigation method, literature method and oral history method to study the evolution of the evolution of the dragon and discusses the value logic of the modernization of Chinese folk sports. The research concluded that in the course of the development, it has a positive influence on the value logic of the modernization of Chinese folk sports should follow the comprehensive modernization of policy, content and organization, the core value pursuit, and fully release the value energy of tool and purpose.